Pengaruh Kepemimpinan Demokratis terhadap Kinerja Pegawai di Dinas Pendidikan Kabupaten Sinjai - Nur Wahid; Jumarni Jumarni; Alyas Alyas (Jurnal Ilmu Politik dan Pemerintahan, 2019)
The purpose of the research are to find out the influence of democratic leadership in employee performance in the education office of Sinjai Regency performance in  The type of the research is quantitative. The sample involved in research are eighty seven people for employees and hundred people for society and the sample used in the research is simple random sampling. In collecting data, the researcher used observation, questionnaire, and documentation. Data analysis technique used in this research is descriptive statistical analysis,correlation, and simple regression. Based on the correlation and simple regression the result of the research shows that the influence employees in Education Office of Sinjai Regency. The leadership variable have a influence and have a relationship with employee performance in Education Office of Sinjai Regency